(untitled) (Journal of International Studies, 2024)
This exploratory, diachronic study compares the politics of Islamisation, which have undergone different patterns of development in both Nigeria and Malaysia. Islamisation is defined as an ideological translation of Islamism into policies to “Islamise” the state and society by expanding the scope of the application of Islamic laws and principles. Islamisation in Malaysia has been implemented steadily and progressively since the 1980s. It involves the “inculcation of Islamic values” in a wide range of aspects of society, including the economy. The Islamic penal code or hudud enactments were legislated in two states, but held in abeyance due to their unconstitutionality. In contrast, Nigeria observed the sudden and erratic implementation of hudud in 12 northern states in 1999, along with other bureaucratic adjustments. Adopting an interpretative case study approach of the comparative method of Arend Lijphart, we explain the two contrastive case studies of the ideological translation of Islamism by analysing the manner in which various political opportunities and structural constraints in the respective cases have shaped the Islamisation process. Data gathering was based on an extensive review of the related body of literature. Analysis was conducted using a social movement theoretical framework based on a structured, focused comparison. The dynamic conceptualisation of the state as a set of institutions, which is continually and dialectically reshaped by contentious processes, captures how the bureaucratisation and judicialisation of Islam have modified the nature of state structures and the structure of political opportunities, which in turn allows for additional channels of influence for Islamic activists.